Regional Disparities and the Electricity Sector in Indonesia 2019-2021 - Sari, Yetti Anita (Media Komunikasi Geografi, 2025)
The electricity sector played an important role in the fulfillment of daily consumption and economic growth, a growing economy was characterized by an increase in gross regional domestic products. Economic growth became the basis of development equity, if the value of regional economic growth was unbalanced it would lead to regional disparity.  The aims of this case study were to analyzed Indonesia's regional disparity in 2019-2021, and to analyze the effect of the electricity sector on Indonesia's regional disparity in 2019-2021. The data used was derived from the Central Bureau of Statistics including data on the number of household electricity consumers, the number of industrial electricity consumers, total population, and per capita income. The methodology of this research was Williamson Index to determine regional disparity. Statistic regression test to analyze the influential factors. The methodology of this research was Williamson Index to determine regional disparity and statistic regression test to analyze the influential factors. The results of this case study were as follows. The value of Williamson index results of provinces in Indonesia is below 0.5, the average inequality trend in Indonesia is relatively stable, at 0.103088 (2019), 0.104359 (2020), and 0.103324 (2021). The electricity sector factor has a significant effect on regional inequality, both household and industrial electricity customer variables.